Exploring financial reporting quality: Evidence from Indonesian local governments - Nuswantoro, Muhammad Adjie; Rahmawati, Evi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study examines the influence of government personnel competence, goods and services expenditure, and infrastructure availability on the quality of local government financial reporting in Indonesia, with local government size as a moderating variable.Design/Methodology/Approach: This quantitative study uses secondary data from local government financial statements in 2020. The sample consisted of 537 local governments selected through purposive sampling. Data were analyzed using Moderated Regression Analysis (MRA).Research findings: The finding show that government personnel's competence positively affects financial reporting quality. Goods and services expenditure has an adverse effect, while infrastructure availability has no significant effect. Local government size weakens the effect of personnel competence, strengthens the effect of goods and services expenditure, and does not moderate the relationship between infrastructure and reporting quality.Theoretical Contribution/Originality: This study offers a novel perspective by empirically examining the interaction between organizational size and key internal factors (human competence, goods and services expenditure, and infrastructure) that influence the quality of local government financial reporting. It extends agency theory by showing that in decentralized public institutions, the effectiveness of internal mechanisms is contingent upon the scale and complexity of the organization.